Application of the container waste glass in foamed glass production - Sonja Smiljanić; Matjaž Spreitzer; Jakob König (Open Ceramics, 2023)
We report on foamed glass production from container glass cullet, foaming couple carbon/Mn3O4, and crystallization inhibitors (fluxing agents, aluminum oxide and phosphates) under an oxygen-free atmosphere. We study the influence of the content of the inhibitors on the density, porosity, crystallinity, and thermal conductivity of the foamed samples. We observe that the amounts of fluxing agents determined to effectively decrease the crystallization (5 wt%) prevent effective foaming and were thus decreased. By decreasing the content of the fluxing agent to 2 wt%, the densities of the foamed samples are decreased. With the addition of phosphates to the mixtures, crystalline content, open porosity and thermal conductivity are decreased. However, the obtained foamed samples remain mainly open porous with density and thermal conductivity in the ranges 140–168 kg m−3 and 57–66 mW m−1K−1, respectively.